1990
DOI: 10.1111/j.1749-6632.1990.tb42376.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Initiation of Myelination by Schwann Cells

Abstract: The rapid morphologic changes in Schwann cells and in their relationships to axons during the transition from the premyelinating to the myelinating state have been known for more than 15 years. The sorting of axons by dividing Schwann cells, the establishment of a 1:1 relationship between a postmitotic Schwann cell, and the onset of myelin sheath formation have all been described in detail. However, the chain of molecular events and mechanisms by which these morphologic changes are regulated has not been eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 14 publications
3
49
0
3
Order By: Relevance
“…To further assess the role of Sirt2 signaling for SC myelination, we used dorsal root ganglion (DRG)/SC cocultures, a valuable model for studying axon-glia interactions during myelin formation (35,36). Consistent with our in vivo data, Sirt2 knockdown exclusively in SCs by lentivirus-mediated delivery of Sirt2 siRNAs significantly reduced the number of anti-MBP-labeled myelin profiles (Fig.…”
Section: Manipulation Of Par-3 Acetylation Status and Apkc Activationsupporting
confidence: 62%
“…To further assess the role of Sirt2 signaling for SC myelination, we used dorsal root ganglion (DRG)/SC cocultures, a valuable model for studying axon-glia interactions during myelin formation (35,36). Consistent with our in vivo data, Sirt2 knockdown exclusively in SCs by lentivirus-mediated delivery of Sirt2 siRNAs significantly reduced the number of anti-MBP-labeled myelin profiles (Fig.…”
Section: Manipulation Of Par-3 Acetylation Status and Apkc Activationsupporting
confidence: 62%
“…Tissue-culture studies have shown that four agents, NGF (Wood et al, 1990;Bahr et al, 1991), progesterone (Koenig et al, 1995), insulin-like growth factor-1 (Russell et al, 1998), and brainderived nerve growth factor (Chan et al, 2001) can sustain or increase the myelination of small axons in vitro. Our in vitro data have shown that GDNF is another agent capable of sustaining the myelination of nerve fibers.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that determine the myelinated phenotype are not completely understood. Many investigators presume that specific axolemmal molecular signals are involved (Wood et al, 1990), but some data suggest that axonal caliber may be sufficient (Voyvodic, 1989); in general, unmyelinated fibers are smaller and myelinated fibers are larger. This study demonstrates that the administration of high doses of a growth factor to rats can change the phenotype of axons from unmyelinated to myelinated.…”
Section: Introductionmentioning
confidence: 99%
“…L1 promotes neuronal survival, neurite outgrowth (Lemmon et al, 1989;Appel et al, 1993;Chen et al, 1999;Kleene et al, 2001;Dong et al, 2003), and synaptic plasticity, as shown by modification of synaptic efficacy both in vitro and in vivo as well as in learning and memory as seen in L1-deficient mice and humans (Luthi et al, 1996;Fransen et al, 1998a,b;Tiunova et al, 1998;Wolfer et al, 1998;Demyanenko et al, 1999;Pradel et al, 2000;Law et al, 2003;Saghatelyan et al, 2004;Venero et al, 2004). Furthermore, L1 is involved in myelination in the central and peripheral nervous systems (Seilheimer et al, 1989;Wood et al, 1990;Haney et al, 1999;Barbin et al, 2004). We have shown previously that L1 influences differentiation of neural stem cells into neurons in vitro (Dihné et al, 2003).…”
Section: Introductionmentioning
confidence: 99%